The Food's Quality Analysis of Canteen in Syarif Hidayatullah State Islamic University Jakarta - Witri Ardini; Siti Nur Aisyah Jauharoh; Erike A. Suwarsono (The Avicenna Medical Journal, 2020)
Background: Food is an important requi-rement supporting the human activities, including academic activities on campus. The composition and quality of nutrients, both macro, and micronutrients in a diet, plays an important role in ensuring the availability of energy sources for daily activities and long-term health. This study is a preliminary study to evaluate the nutritional value of food provided in the canteen of campus.Method: This research will use a cross-sectional design on food samples sold in the canteen of Syarif Hidayatullah State Islamic University Jakarta. The macronutrient composition analysis was calculated using a list of foodstuffscompositions.Results: Most of the packaged food menu do not meet the macronutrient composition in a manner of balanced nutrition. The dominant side dish is chicken, the fat composition is higher than the recommendation due to fried processing. The portion of rice is not standard on various packages, with an average of 1.6 servings of standard rice. The content of vegetables is minimal. A snack menu is predominantly carbohydrate foods with a moderate to high sugar content, with minimal ber content, and processed by frying.Conclusion: The nutritional quality of the food menu in the canteen has largely not yet fulfilled the recommended macronutrient composition.